University in the time of Covid-19 - Fonzo, Concetta (Community Notebook. People, Education and Welfare in the Society 5.0, 2021)
The lockdown has brought to the centre of political, scientific, academic and economic debate the topic of distance learning, access through the use of digital tools to educational and training pathways and the skills, not only digital, that boys and girls, students of all levels of education must possess in order to actively participate in the inevitable and unstoppable process of digitisation that is underway.